HALP score and GNRI: Simple and easily accessible indexes for predicting prognosis in advanced stage NSCLC patients. The İzmir oncology group (IZOG) study - Güç, Zeynep Gülsüm; Alacacıoğlu, Ahmet; Kalender, Mehmet Eren; Oflazoğlu, Utku; Ünal, Sinan; Yıldız, Yaşar; Salman, Tarık; Küçükzeybek, Yüksel; Tarhan, Mustafa Oktay (Frontiers in Nutrition, 2022)
Objective: The Hemoglobin, Albumin, Lymphocyte, and Platelet (HALP) Score and the Geriatric Nutrition Risk Index (GNRI) are used as prognostic factors in different types of cancers. In this study we analyzed the prognostic value of the HALP Score and the GNRI calculated prior to first-line treatment in patients diagnosed with de novo metastatic non-small cell lung cancer (mNSCLC). Material and Methods: De novo mNSCLC patients were retrospectively evaluated from January 2016 to December 2019. Patients with Driver's mutation, severe comorbidities, active infection, or insufficient organ function, and those receiving anti-inflammatory treatment were excluded from the study. Optimal cut-off points for the HALP score and the GNRI were calculated with the receiver operating characteristic (ROC) curve analysis. Predictive factors for overall survival (OS) were assessed with univariate and multivariate Cox proportional hazard analyses, and OS was studied with the Kaplan-Meier analysis. Results: The study included 401 patients in total. In the ROC curve analysis, the cut-off points were found 23.24 (AUC=0.928; 95% CI: 0.901-0.955, p<0.001) for HALP, and 53.60 (AUC=0.932; 95% CI: 0.908-0.955, p<0.001) for GNRI. Groups with lower HALP scores and lower GNRI had significantly shorter OS compared to those with higher HALP scores and GNRIs. Univariate analysis showed that male gender, smoking, high ECOG score, low HALP score and low GNRI were associated with worse survival rates. Multivariate analysis showed that low HALP score (HR=2.988, 95% CI: 2.065–4.324, p<0.001); low GNRI score (HR=2.901, 95% CI: 2.045–4.114, p<0.001) and smoking history (HR=1.447, 95% CI: 1.046–2.001, p=0.025) were independent factors associated with worse OS rates. Conclusion: Our study showed the HALP score and the GNRI to be of prognostic value as simple, cost-effective, and useful markers that predict OS in de novo mNSCLC patients. Keywords: Geriatric nutritional risk index (GNRI), non-small cell lung cancer, hemoglobin-albumin-lymphocyte-platelet score, prognostic